RETRACTED: Fossil Energy Demand and Economic Development in BRICS Countries - Wang, Hong; Asif Amjad, Muhammad; Arshed, Noman; Mohamed, Abdullah; Ali, Shamsher; Haider Jafri, Muhammad Afaq; Khan, Yousaf Ali (Frontiers in Energy Research, 2022)
Energy is considered the oxygen of an economy fueling all economic activities. Energy utilization and its type have an intertemporal and size-based effect on economic development. Therefore, this study empirically analyzes the relationship of fossil energy consumption with economic development in the case of BRICS countries between 1990 and 2019. Fully modified ordinary least squares is used with the quadratic function of coal, oil, and gas consumption to assess the size-based effect across time. This study shows that coal and natural gas consumption follows the inverted U-shaped relationship with HDI, while coal consumption shows a negative relationship with HDI. Hence, coal and gas energy assists in development when its share is small, while over-consumption hampers development. The BRICS countries should optimize coal and gas consumption with respect to economic development. Reducing fossil energy should be substituted with alternative clean energy resources by using advanced technology such as the gasification process.